SOSIALISASI RAMBU LALU LINTAS PERLINTASAN KERETA API DI MTS NEGERI 5 KARANGANYAR (JPMPPI (Jurnal Pengabdian Masyarakat), 2022)
Signs are symbols or symbols that function as orders, instructions, prohibitions, and warnings. One of the signs that must be considered in traffic is the signs at railroad crossings. Signs at railroad crossings, especially at level crossings. At level crossings, there are signs whose meaning or purpose is not widely known by the public. The signs are abstract two-lane railroad crossings, warnings not to go on, railroad crossings without gates, and railroad crossings with gates. This socialization was carried out at MTs Negeri 5 Karanganyar. This socialization aims to increase public education from an early age about traffic signs, especially at level crossings that are often passed by the community in their daily activities.